DEVELOPMENT OF NATURAL COOL BATH (PAS) TIMURAN TOURISM OBJECT TO INCREASE THE INCOME OF MARIAH JAMBI VILLAGE COMMUNITY, SIMALUNGUN REGENCY - Chinthia Gelvani Silalahi; Muhammad Husni Thamrin (Indonesian Journal of Social Sciences, Policy and Politics, 2025)
The Natural Cool Bath (PAS) Timuran tourist attraction has great potential to increase the income of the Mariah Jambi Village community, but this potential has not been optimally managed. This study aims to identify the existing management conditions, analyze supporting and inhibiting factors, and formulate development strategies for the Natural Cool Bath (PAS) Timuran tourist attraction in Mariah Jambi Village, Simalungun Regency to increase community income. The research method used is descriptive research with a qualitative approach. Data collection was carried out through interview techniques, observation, and documentation. Data were analyzed qualitatively using Tourism Management Theory with indicators of Tourism Development components according to Cooper et al. (1995), namely Attraction, Accessibility, Amenities, and Ancillary Service. The results of this study indicate that PAS Timuran has attractive natural potential but still faces challenges in terms of accessibility, facilities, and promotion. Current management is carried out independently with community involvement through Pokdarwis, but coordination with other stakeholders still needs to be improved. The existence of this tourist attraction has had a positive economic impact on the community, although efforts are still needed to improve skills and knowledge in sustainable tourism management to maximize its economic potential.